Consistency Expectations: Materiality Judgments and Audit Firm Structure. - Morris, Michael H.; Nichols, William D. (The Accounting Review, 1988)
Abstract This study examines empirically three aspects of auditor materiality judgments: (1) their association with publicly available financial information, (2) whether materiality judgment consensus differs across Big Eight audit firms, and (3) whether judgment consensus is correlated with audit firm structure. The results suggest that nine publicly available financial measures explain a significant portion of the variability in auditor materiality judgments, thereby raising a question about potential information in auditors' interest-capitalization consistency exceptions. Although publicly available financial information was found to be significantly associated with materiality judgments in each Big Eight firm, the judgment consensus of consistency opinion decisions varied among individual Big Eight firms. Not only were there significant differences in judgment consensus among firms but also a significant positive association was found between audit judgment consensus and the degree of audit structure, thereby providing empirical evidence that audit structure may influence audit judgment.